2016
DOI: 10.1038/onc.2016.358
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 induces LOXL2-mediated collagen stabilization and deposition in the extracellular matrix to drive lung cancer invasion and metastasis

Abstract: Lung cancer is the leading cause of cancer-related death, primarily due to distant metastatic disease. Metastatic lung cancer cells can undergo an epithelial-to-mesenchymal transition (EMT) regulated by many transcription factors, including double-negative feedback loop between the microRNA-200 (miR-200) family and ZEB1, but the precise mechanisms by which ZEB1-dependent EMT promotes malignancy remain largely undefined. While the cell-intrinsic effects of EMT are important for tumor progression, the reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
133
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(160 citation statements)
references
References 57 publications
(95 reference statements)
16
133
1
1
Order By: Relevance
“…These observations are in line with this study that cell proliferation and migration activity of HCFs are significantly inhibited by interfering with the expression of ZEB1 (Figure A,B), and these findings are according with that miR‐590‐3p suppress cell proliferation and migration of cardiac fibroblasts (Figure C,D) and cancer cells . Furthermore, ZEB1 significantly induces the mRNA expression of Col1A1 and Col3A1 of ECM‐related genes to dive lung cancer invasion and metastasis, and this report is according to our study that the mRNA and protein expressions of Col1A1 and Col3A1 are significantly decreased by interfering with the expression of ZEB1 (Figure C,D). These results demonstrate that ZEB1 promotes the proliferation, differentiation, migration and collagen synthesis of cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 90%
“…These observations are in line with this study that cell proliferation and migration activity of HCFs are significantly inhibited by interfering with the expression of ZEB1 (Figure A,B), and these findings are according with that miR‐590‐3p suppress cell proliferation and migration of cardiac fibroblasts (Figure C,D) and cancer cells . Furthermore, ZEB1 significantly induces the mRNA expression of Col1A1 and Col3A1 of ECM‐related genes to dive lung cancer invasion and metastasis, and this report is according to our study that the mRNA and protein expressions of Col1A1 and Col3A1 are significantly decreased by interfering with the expression of ZEB1 (Figure C,D). These results demonstrate that ZEB1 promotes the proliferation, differentiation, migration and collagen synthesis of cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 90%
“…Next, this step should be performed and the definite mechanism behind need to be explored. LOXL-2 was suggested to be specifically involved in cell adhesion and senescence in earlier study and recently, it was proved as a role in regulating angiogenesis through collagen IV scaffolding [ 43 ] and to participated in the mechanisms in many tumors and carcinoma, like the effect on proliferation of hepatocellular carcinoma, mediating transition and proliferative growth of dormant tumor cells, and drive lung cancer invasion and metastasis [ 44 46 ] . However, there was no report of the role of LOXL2 in the pathogenesis of CD or ITB, and we found that LOXL2 distribution was lower in CD patients when compared with ITB, but due to the limited number of samples, we did not validated LOXL2 in a larger sample and the mechanisms warrant further investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the tumor microenvironment in initiating EMT and metastasis and the role of tumor cell EMT in remodeling the tumor microenvironment can also be further explored (Gibbons et al, 2009; Peng et al, 2016), using appropriate experimental model systems. The molecular profile of a tumor may be influenced by a combination of cancer cell of origin, somatic alterations, and microenvironment.…”
Section: Resultsmentioning
confidence: 99%